1998
DOI: 10.1093/jn/128.4.677
|View full text |Cite
|
Sign up to set email alerts
|

Obese Gene Expression in Porcine Adipose Tissue Is Reduced by Food Deprivation but not by Maintenance or Submaintenance Intake

Abstract: The relationship between obese gene expression and energy intake was determined in pigs of various body weights. With ad libitum consumption, expression increased (P < 0.001) with body weight from 55 to 163 kg. Obese mRNA relative abundance was correlated with fat mass (r = 0.74, P < 0.0001) and percentage of fat (r = 0.72, P < 0. 0001). Obese expression was also evaluated at 159 kg (initial weight) and ad libitum, maintenance or 23% of maintenance intake for 28 d. Obese mRNA was independent of treatment (P > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 31 publications
2
18
2
Order By: Relevance
“…We observed a decrease in serum leptin following feed removal at 12 h. This was similar to other studies that found leptin was depressed following a short-term fast (Bergendahl et al 2000). The fact that leptin mRNA expression in fat tissue was lower in feed-deprived animals is consistent with other studies utilizing pigs (Spurlock et al 1998, Barb et al 2001. The decrease in leptin in recently weaned pigs utilized in experiment 2 was rather dramatic and occurred within 12 h. This may be due to differences in percentage body fat and/or differences in metabolism between adult and young animals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed a decrease in serum leptin following feed removal at 12 h. This was similar to other studies that found leptin was depressed following a short-term fast (Bergendahl et al 2000). The fact that leptin mRNA expression in fat tissue was lower in feed-deprived animals is consistent with other studies utilizing pigs (Spurlock et al 1998, Barb et al 2001. The decrease in leptin in recently weaned pigs utilized in experiment 2 was rather dramatic and occurred within 12 h. This may be due to differences in percentage body fat and/or differences in metabolism between adult and young animals.…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in leptin in recently weaned pigs utilized in experiment 2 was rather dramatic and occurred within 12 h. This may be due to differences in percentage body fat and/or differences in metabolism between adult and young animals. Upon refeeding, serum leptin concentrations increased within 12 h. Leptin mRNA expression was not increased following refeeding for 24 h. There is evidence that insulin may be the acute regulator of leptin in rodents (Saladin et al 1995) and pigs (Spurlock et al 1998). It has also been hypothesized that regulation of leptin secretion is accomplished via neural inputs into adipose tissue (Youngstrom & Bartness 1995).…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, leptin expression is significantly reduced by fasting in all species studied to date. (10)(11)(12)20) In fasted pigs, ( 0.05, n5 48) and 77.0% of control at 10 h after injection (p, 0.05, n5 8).…”
Section: Discussionmentioning
confidence: 95%
“…Fasting results in a dramatic downregulation of leptin protein and mRNA in rodents and humans (10)(11)(12) and a modest down regulation of leptin mRNA in the pig. (20) One potential mechanism underlying the profound effects of fasting on leptin expression may be the glucose-sensing, hexosamine biosynthetic pathway, which was recently reported to regulate leptin expression in adipose and muscle tissue of rats. (19) Additionally, metabolic hormones that are altered with fasting such, as insulin, glucocorticoids, and thyroid hormone, regulate leptin expression.…”
Section: Introduction I N F La M M a Tio N Is C H A R A Cte Rized By mentioning
confidence: 99%
“…A high abundance of plasma leptin is associated with greater adiposity in pigs (Robert et al 1998;Spurlock et al 1998;Owens et al 1999) and other mammals (Lissner et al 1999;Phillips et al 1999;Timtchenko et al 1999). In cattle, Chilliard et al (1998) have shown that leptin is positively correlated to adipocyte volume in both Holstein and Charolais breeds, with the correlation slightly higher in overfed (r = 0.73, P = 0.0028) than in underfed (r = 0.68, P = 0.0021) cattle.…”
Section: Resultsmentioning
confidence: 99%